ENDOGENOUS GROWTH THEORY : PENGARUH BELANJA KESEHATAN DAN PENDIDIKAN TERHADAP EKONOMI - Ming Shen; Azka Dhiya; Kathya Kathya (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2021)
Indonesia has a considerable amount of human resources. Those resources should be empowered more in order to contribute to the economy. The proposition that can be taken to manage the plans is investing in human resources through the form of education and health. When the society becomes healthier and skillful, then they can contribute positively to the economy through productivity increase. The intervention of the government’s role in both sectors can be through government spending such as making programs or facilities that are expected to benefit the society. Therefore, this literature intends to see whether the government spending on the education and health sectors can contribute positively to the economy or even the opposite, using the OLS method with a research span from 1990 to 2019. The results show that health and education spending significantly affects the economy. This indicates that workers in Indonesia are getting skillful and also supported by their health, so that the productivity is well maintained. Both of these statements reflect that health and education spending in Indonesia has an impact on the economy through productivity increase.